Ancient Maya Indians of Central America [videorecording] - Encyclopedia Britannica Educational Corporation (Chicago Encyclopedia Britannica Educational Corporation, 1991)
Describes the ancient history Mayan civilization and the development of their culture.
Film adaptation : William Peltz.
VHS.
Keywords: Mayas -- Antiquities; Mayas -- History